Legal Design Perspectives Theoretical and Practical Insights from the Field - Ducato, Rossana; Strowel, Alain (Ledizioni, 2021)
Over the last few years, Legal Design has grown as a field of research and practice. The potential of design in the legal domain has been investigated and experimented in various sectors such as access to justice, dispute resolution, privacy indicators, policy prototyping, contractual negotiation. Being an interdisciplinary area of study, Legal Design combines different disciplines and methodologies and relies on insights from legal practice. This book intends to contribute to the study and advancement of Legal Design by presenting different voices and perspectives from scholars and practitioners active in this field. The volume brings together critical essays on the nature and methods of Legal Design and illustrations from the practice. The contributions provide the readers with the state of the art of Legal Design and a prospective outline of its future development.